Poverty, Demographic Characteristics, and Public Policy in Cis Countries - Ahmad, Ehtisham (Washington, D.C. : International Monetary Fund, 1993)
The demographic characteristics of different regions in the former Soviet Union influence the nature of poverty in the newly successor independent states of the FSU. Despite a common policy inheritance, major adjustments are needed in the major social protection instruments to reflect differences in demographics along with a changing resource base.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet